Soluble trace metals associated with atmospheric fine particulate matter in the two most populous cities in Vietnam. (October 2022) - Hien, To Thi; Chi, Nguyen Doan Thien; Huy, Duong Huu; Le, Hoang Anh; Oram, David E.; Forster, Grant L.; Mills, Graham P.; Baker, Alex R.
Abstract: Hanoi and Ho Chi Minh City (HCM), the most populous cities in Vietnam, have received increasing global attention because of their poor air pollution status. As part of the recent UK-Vietnam 2-Cities project, the concentrations of trace metals in fine particulate matter have been characterized. 24-hour samples of PM2 were collected at 2 sites in Hanoi and 3 sites in HCM during two 4-week periods in September/October 2018 and March 2019. The soluble fraction of 15 trace metal(oid)s (Fe, Al, Mn, Ti, Zn, V, Cu, Ni, Co, Cd, Pb, Th, Cr, As, and Sb) bound to PM2 were analyzed by ICP-MS. The results show that Zn was the most abundant soluble metal in PM2 in both cities, with very large numbers of road vehicles (e.g. tyre wear) likely contributing in both cities and non-ferrous metal production being a substantial additional source in Hanoi. Fe and Al, derived from crustal sources, were the dominant metals after Zn. Most trace metals concentrations in Hanoi were higher than in HCM, especially toxic metals such as Pb, Cd, Cr and As. V and Ni were the only two metals having higher concentrations in HCM than in Hanoi, likely due to shipping emissions (combustion of heavy fuel oil) that strongly affect the air quality in HCM. Coal-power plants and non-ferrous metal production are likely to be the major sources of trace metals in Hanoi. Health risk assessment shows that a high carcinogenic risk exists for inhalation exposure of soluble trace metals bound to PM2 in both cities. Highlights: The first evaluation of the levels of soluble trace metals in fine PM in Hanoi and HCM, the two biggest cities in Vietnam. Zn was most abundant (motorcycles significant contributor). Hanoi > HCM for most metals except V and Ni. Suggest potential emission sources of soluble trace metals in the two cities.